Computational modelling and analysis of transverse liquid composite moulding processes. (April 2023) - Lee, J.; Duhovic, M.; Allen, T.; May, D.; Kelly, P.
Abstract: Transverse (through-thickness) impregnation variants of Liquid Composite Moulding (LCM) processes result in relatively fast fill times due to the short resin flow path. In a recently developed transverse LCM process termed Resin Transfer Pressing (RTP), compaction drives resin from a saturated carrier material into a dry reinforcement material. In this work, a model has been developed to simulate the entire family of transverse LCM processes, including RTP and Compression Resin Transfer Moulding (CRTM). Under the assumption of one-dimensional flow, simulations are carried out to predict the process time, fluid pressure, effective stress, and fibre volume fraction distribution through the thickness for these processes. It is shown how commonly made assumptions such as quasi-steady flow and uniform through-thickness deformation introduce significant errors in manufacturing process predictions, such as the tool velocity and homogenisation time, especially for transverse processes involving direct tool compaction of the fibre preform.